Breastfeeding with HIV in a high-income setting: equipoise and beyond – time to question the zero-risk policy (Swiss Medical Weekly, 2025)
With the use of combined antiretroviral therapy (cART), it has become possible to completely and permanently suppress human immunodeficiency virus (HIV) replication. Successful treatment with combined antiretroviral therapy not only makes HIV infection a treatable chronic disease with a near-normal life expectancy, but also reliably prevents horizontal and also vertical virus transmission. In principle, this allows us to dispense with certain preventive measures from the pre-cART era. However, HIV prevention recommendations tend not to be adjusted until it has been proven beyond any doubt that there is no associated risk. This zero-risk strategy still makes HIV infection a special case and contradicts standard medical practice, which almost always also entails some acceptable risk. This hesitant attitude delays adaptations of care and contributes to the stigmatisation of those affected. In addition, it might even violate the ethical principles of beneficence and justice.In this context, there is still an ongoing debate as to whether the credo “U = U” (undetectable = untransmittable) applies to all aspects of vertical transmission. While there is consensus about the safety of vaginal delivery in case of an undetectable maternal viral load, Switzerland is still the only country that has also refrained from providing post-exposure prophylaxis to newborns since 2016 in such cases.Furthermore, when we last revised our Swiss recommendations for the prevention of vertical transmission in 2018, we assumed a balance (equipoise) between the benefits and potential risks of breastfeeding with HIV under optimal conditions. We proposed a shared decision-making process to allow the expectant mother to make her own well-considered decision which is then unconditionally supported by the care team. However, the decision and the associated responsibility is basically left to the woman. Most high-income countries have meanwhile adopted this procedure.Based on a literature review summarised in this article, the question arises as to whether this approach is still justified. We came to the conclusion that the potential risks of breastfeeding with HIV are being overemphasised, as benefits of breastfeeding, including reductions in morbidity and mortality for both mother and child appear to clearly outweigh these apparently very low risks, even in high-income settings. We therefore believe that breastfeeding with HIV should be favoured and encouraged and not just supported under optimal circumstances and that the care teams should take a clear position in this regard. This will facilitate decision-making for affected women, reduce stigma, relieve the parent(s) of taking on primary responsibility for the decision and further “normalise” HIV infection.